In Vitro culture of rose species (Rosa ssp.)via axillary bud growth - De la Rosa, Zosimo S.; Belarmino, Marilyn M. (Annals of Tropical Research, 2007)
The utilization of nodal stem cuttings containing dormant axillary buds as explants for plant production of two rose species; Rosa chinensis cv. ‘Old Blush’ and R. centifolia cv. ‘Petite de Hollande’ was demonstrated in this study. This propagation technique required the breaking of dormant axillary buds by aseptically culturing them in agar-solidified Woody Plant Medium (WPM) added with 0.5, 1.0, and 2.0 mg l-1 of 6-benzylaminopurine (BAP) or, a combination of 2.0 mg l-1 BAP and 0.01 mg l-1 naphthalene acetic acid (NAA). Production of multiple adventitious shoots from one nodal stem explant was obtained after three months of culture in medium supplemented with 1.0 or 2.0 mg l-1 BAP. Four types of plant morphology; single shoot (type 1), multiple shoots with normal leaves (type 2), cluster of tiny shoots with curly leaves (type 3), and single shoot with callus at the base (type 4) were observed from the axillary bud-derived plantlets. The rooting of plantlets was induced in WPM containing 0.25 to 1.0 mg l-1 of indole-butyric acid (IBA) or, 2.0 mg l-1 of indole-3-acetic acid (IAA).